PROFIL KELARUTAN LIMBAH MINYAK BUMI DALAM AIR AKIBAT PENGARUH SURFAKTAN NONIONIK DAN LAJU PENGADUKAN - Charlena, Charlena (CHEMISTRY PROGRESS, 2009)
Petroleum waste is classified as a dangerous waste that cause pollution and damage the environtment.The remediation of petroleum polluted soil could be done by microorganism capability. Additional ofnonionic surfactant and stirring rate would make soil dispersed well in water, facilitating good contactbetween microorganism and petroleum carbon as its feed. In this research, Tween 80 and Brij 35 wereused as surfactants. The observed parameters were concentrations and stirring rates. Surfactantconcentration was selected based on surface tension value and emulsion stability. The highest emulsionstability for Tween 80 observed was 0.24% at concentration 0.0175%, while for Brij 35 equal to 0.22% atconcentration 0.0150%. Stirring rates were applied 100, 120, and 140 rpm, successively based on liquidTotal Petroleum Hydrocarbon (TPH) value. Liquid TPH value at 100, 120, and 140 rpm for Tween 80 andBrij 35 were 0.25, 0.32, 0.40 and 0.36, 0.55, 0.74%, successively. Liquid TPH depicted amount of oil thatwas dispersed into the water. The other parameters such as solid TPH and Chemical Oxygen Demand(COD) obtained for 140 rpm were 15.56% and 41235 mg/L for Tween 80 while for Brij 35 equal to 16.55%and 41717 mg/LÂ Keywords : petroleum waste, nonionic surfactant, stirring rate